A cross-sectional study of magnitude of diabetes among individuals attending health camp in an urban area of Solapur - Sapkale, Mayur K.; Gaikwad, Lagdir L.; Kabra, Pratyush R.; Jatti, Gajanan M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes is a significant contributor to non-communicable diseases related morbidity and mortality worldwide. A significant proportion of diabetes cases still remain undiagnosed in India. Glycosylated haemoglobin HbA1c ≥6.5% is a convenient and reliable alternative to plasma glucose tests to diagnose diabetes. Methods: An observational cross-sectional descriptive study was conducted among all individuals attending Health Camp at Solapur after taking institutional ethical committee (IEC) approval. Out of 299 individuals who attended the health camp only 126 individuals gave written informed consent to collect venous blood samples to measure their HbA1c levels. HbA1c cut-offs for diabetes and prediabetes was determined based on the recommended values of American Diabetes Association. Results: Magnitude of diabetes was (27.8%) and Prediabetes was (15.9%) among the study participants according to their HbA1c levels. Statistically significant association was seen between prediabetes diabetes and age, gender and hypertensive while no significant association was seen with residence and socioeconomic status. Conclusions: The study reported magnitude of diabetes among study participants was 35 (27.8%) of which 29 (23.01%) study participants were newly detected. Screening for NCD’s like diabetes is very important for early diagnosis and prompt treatment especially among advancing age, female and hypertensive individuals for halting the transition of prediabetes to diabetes.